Overview of educational level, nutritional knowledge, and dietary adherence among patients with type 2 diabetes mellitus - Adelina Ramadhani (Arsip Keilmuan Gizi (AKG), 2024)
Type 2 Diabetes Mellitus (DM) is a chronic disease characterized by impaired insulin action, resulting in uncontrolled blood glucose levels. Dietary management, including adherence to recommended meal timing, portion size, and food choices, is a fundamental component of type 2 DM management. However, dietary adherence among patients with type 2 DM remains a major challenge in routine health care practice. This study aimed to describe the educational level, nutritional knowledge, and dietary adherence among patients with type 2 DM. This quantitative study employed a cross-sectional design. The study subjects were patients with type 2 DM receiving outpatient care at Karawang District Hospital in 2017, selected using purposive sampling. Data were collected through interviews using structured questionnaires to obtain information on subject characteristics, educational level, nutritional knowledge, and dietary adherence. The results showed that none of the subjects demonstrated adherence to the recommended dietary guidelines. These findings indicate that poor dietary adherence remains a key issue in the management of type 2 DM, regardless of patients’ educational level and nutritional knowledge. This condition highlights the need for strengthening continuous nutrition education and implementing more intensive and accessible nutrition counseling approaches. Increasing patient engagement in nutrition counseling services is expected to improve understanding and application of appropriate dietary management, thereby supporting optimal glycemic control in patients with type 2 DM.